Financial integration and macroeconomic volatility in the ECCU - Grenade, Kari ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2004)
Investigates the relationship between financial integration and macroeconomic volatility in the countries of the Eastern Caribbean Currency Union. Provides empirical evidence on the link betwee financial integration and the volatilities in the growth of real output, investment and private consumption.